2017
DOI: 10.5194/aab-60-347-2017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation with <i>Rhizopus oryzae</i> or <i>Chrysonilia crassa</i> on growth performance, blood profile, intestinal microbial population, and carcass traits in broilers exposed to heat stress

Abstract: Abstract. Dietary supplementation of additives has recently been part of strategies to deal with the detrimental effects of heat stress (HS) on the performance and carcass traits in broiler chicks. This study aimed to investigate the effect of dietary supplementation with the fungi Rhizopus oryzae or Chrysonilia crassa on growth, blood profile, intestinal microbial population and carcass traits in broiler chicks subjected to HS. R. oryzae and C. crassa are filamentous fungi isolated from the ileum of indigenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 39 publications
4
29
0
Order By: Relevance
“…Data of globulin were obtained from the difference between the values of total protein and albumin in serum. The counts of certain bacteria in the intestinal digesta of broilers were determined according to Sugiharto et al (2017b) with few modifications. For enumeration of coliform bacteria and lactose-negative enterobacteria, samples were cultured on MacConkey agar.…”
Section: Methodsmentioning
confidence: 99%
“…Data of globulin were obtained from the difference between the values of total protein and albumin in serum. The counts of certain bacteria in the intestinal digesta of broilers were determined according to Sugiharto et al (2017b) with few modifications. For enumeration of coliform bacteria and lactose-negative enterobacteria, samples were cultured on MacConkey agar.…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of fungal starter cultures was adopted from Sugiharto et al (2017b) with few modifications. The inoculum of Ch.…”
Section: Preparation Of Starter Culturesmentioning
confidence: 99%
“…The measurements of villus height of each intestinal segment were performed using an optical microscope fitted with a digital camera (Leica Microsystems GmbH, Wetzlar, Germany). The counts of bacteria in ileum and caecum of broiler chickens were determined according to Sugiharto et al (2017b) with few modifications. Total coliform and lactose-negative enterobacteria were enumerated on MacConkey agar (Merck KGaA, Darmstadt, Germany) as red and colourless colonies, respectively, after aerobic incubation at 38°C for 24 hours.…”
Section: In Vivo Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of trials have revealed the high predatory efficacy of preparations based on fungi against a wide range of helminths colonizing the gastrointestinal tract of various species, such as the filamentous fungi Chrysonilia crassa (9) or Arthrobotrys oligospora (10,11). One of these helminthophags is the predatory fungus D. flagrans, a spore-mycelial biomass of which is contained in Vetom 21.77 and is supposed to antagonize helminths and pathogenic gut microflora.…”
Section: Introductionmentioning
confidence: 99%